Mice transgenic for CD4-specific human CD4, CCR5 and cyclin T1 expression: a new model for investigating HIV-1 transmission and treatment efficacy. - Kieran Seay (Public Library of Science (PLoS), 2013)
Mice cannot be used to evaluate HIV-1 therapeutics and vaccines because they are not infectible by HIV-1 due to structural differences between several human and mouse proteins required for HIV-1 entry and replication including CD4, CCR5 and cyclin T1. We overcame this limitation by constructing mice with CD4 enhancer/promoter-regulated human CD4, CCR5 and cyclin T1 genes integrated as tightly linked transgenes (hCD4/R5/cT1 mice) promoting their efficient co-transmission and enabling the murine CD4-expressing cells to support HIV-1 entry and Tat-mediated LTR transcription. All of the hCD4/R5/cT1 mice developed disseminated infection of tissues that included the spleen, small intestine, lymph nodes and lungs after intravenous injection with an HIV-1 infectious molecular clone (HIV-IMC) expressing Renilla reniformis luciferase (LucR). Furthermore, localized infection of cervical-vaginal mucosal leukocytes developed after intravaginal inoculation of hCD4/R5/cT1 mice with the LucR-expressing HIV-IMC. hCD4/R5/cT1 mice reproducibly developed in vivo infection after inoculation with LucR-expressing HIV-IMC which could be bioluminescently quantified and visualized with a high sensitivity and specificity which enabled them to be used to evaluate the efficacy of HIV-1 therapeutics. Treatment with highly active anti-retroviral therapy or one dose of VRC01, a broadly neutralizing anti-HIV-1 antibody, almost completed inhibited acute systemic HIV-1 infection of the hCD4/R5/cT1 mice. hCD4/R5/cT1 mice could also be used to evaluate the capacity of therapies delivered by gene therapy to inhibit in vivo HIV infection. VRC01 secreted in vivo by primary B cells transduced with a VRC01-encoding lentivirus transplanted into hCD4/R5/cT1 mice markedly inhibited infection after intravenous challenge with LucR-expressing HIV-IMC. The reproducible infection of CD4/R5/cT1 mice with LucR-expressing HIV-IMC after intravenous or mucosal inoculation combined with the availability of LucR-expressing HIV-IMC expressing transmitted/founder and clade A/E and C Envs will provide researchers with a highly accessible pre-clinical in vivo HIV-1-infection model to study HIV-1 acquisition, treatment, and prevention.